PERAN MASJID SEBAGAI SUMBER BELAJAR DALAM PENDIDIKAN AGAMA ISLAM DI SMP ISLAM DARUL ABROR DESA ANGKATAN KECAMATAN ARJASA KABUPATEN SUMENEP - Nurifatul Halifah; Nur Hasan; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This research describes the role of the mosque as a learning resource in Islamic religious education. This research will also answer the questions posed by researchers, that is what is the role of mosques as a learning resource in Islamic religious education, how is the learning process of Islamic religious education in mosques, what are the supporting and inhibiting factors of mosques as learning resources. The research method used is a qualitative approach with the type of case study research. Data collection techniques used are observation, interviews, and documentation. The results of this research indicate that: (1) The program of the mosque is Hifdzul Qur’an in the morning, dhuha prayer in congregation, reciting the Qur’an together, istighosah, tahlil, recitation of the yellow book, training of sermons, bilal, and also speeches, (2) The implementation of learning at the mosque starts in the morning at 06.30 with hifdzul quran activities and ends with muthalaah activities at 20.00 (3) The supporting factors is media or devices that support learning such as the Al-Qur'an, books, prayer mats, mukenah, mic, sound/speaker and the inhibiting factor is difficult to regulate students to follow the lessons on time.